Anti-parasite treatment results in decreased estimated survival with increasing lead (Pb) levels in the common eider Somateria mollissima - Morrill, A. (Proc Biol Sci, 2019)
Field experiments where parasites are removed through treatment and contaminant levels in host tissues are recorded can provide insight into the combined effects of parasitism and contaminants in wild populations. In 2013 and 2014, we treated northern common eider ducks (Somateria mollissima) arriving at a breeding colony with either a broad-spectrum antihelminthic (PANACUR(®)) or distilled water, and measured their blood lead (Pb) levels. Breeding propensity and clutch sizes were inversely related to Pb in both treatment groups. In comparison, a negative effect of Pb on resight probability the following year was observed only in the anti-parasitic treatment (APT) group. These contrasting patterns suggest a long-term benefit to survival of intestinal parasitism in eiders experiencing Pb exposure. The arrival date of hens explained some, but not all, of the effects of Pb. We weigh the merits of different hypotheses in explaining our results, including protective bioaccumulation of Pb by parasites, condition-linked thresholds to costly reproduction and the direct effects of APT on eider health. We conclude that variation in helminth parasitism influences survival in this migratory bird in counterintuitive ways.